Effects of energy spread on brightness and coherence of undulator sources. (24th August 2018) - Geloni, Gianluca; Serkez, Svitozar; Khubbutdinov, Ruslan; Kocharyan, Vitali; Saldin, Evgeni
Abstract : The advent of `diffraction‐limited' storage rings with ultralow emittance poses a question on possible limitations to the (spectral) brightness and coherence due to the electron beam energy spread. This is studied here using semi‐analytical techniques. Abstract : The (spectral) brightness for partially transverse coherent sources such as synchrotron radiation and free‐electron laser sources can be defined as the maximum of the Wigner distribution. Then, the brightness includes information on both coherence and wavefront characteristics of the radiation field. For undulator sources, it is customary to approximate the single‐electron electric field at resonance with a Gaussian beam, leading to great simplifications. Attempts to account for the modified spatial and angular profile of the undulator radiation in the presence of detuning due to energy spread, currently build on the simplified brightness expression derived under the assumption of Gaussian beams. The influence of energy spread on undulator radiation properties is becoming important in view of diffraction‐limited rings with ultralow emittance coming on‐line. Here the effects of energy spread on the brightness of undulator radiation at resonance are discussed, as well as relevant relations with coherence properties.